The Impact Of Information Asymmetry On Esg And Intellectual Capital In Reducing Equity Costs - Firda Ainun Nabila; Erwin Saraswati; Arum Prastiwi (Universitas Muhammadiyah Malang, 2024)
Purpose: This study examines the effect of intellectual capital and ESG disclosures on equity costs, with information asymmetry as a moderating variable. Methodology/approach: This quantitative study uses an explanatory approach, focusing on manufacturing companies listed on the Indonesia Stock Exchange from 2019-2022. Secondary data from annual reports were analyzed using Moderated Regression Analysis. Findings: The results of the study show that intellectual capital disclosure and ESG can reduce the cost of capital. High information asymmetry can weaken the negative relationship between ICD on the cost of capital. Practical implications: For companies with the results of this study, it can be considered to maximize the benefits of ESG ICD disclosure in reducing the cost of capital, companies need to focus on reducing information asymmetry. This can be done through the presentation of more complete, detailed, and verifiable information about ESG and ICD performance. Originality/value: Including information asymmetry as a moderating variable, this study offers a new perspective, highlighting how the effect of intellectual capital and ESG disclosures on equity costs depends on information distribution, a factor previously underexplored.